2011
DOI: 10.1161/atvbaha.110.214031
|View full text |Cite
|
Sign up to set email alerts
|

Role of Shear Stress in Endothelial Cell Morphology and Expression of Cyclooxygenase Isoforms

Abstract: Objective-The goal of this study was to examine the effect of chronic heterogeneous shear stress, applied using an orbital shaker, on endothelial cell morphology and the expression of cyclooxygenases 1 and 2. Methods and Results-Porcine aortic endothelial cells were plated on fibronectin-coated Transwell plates. Cells were cultured for up to 7 days either under static conditions or on an orbital shaker that generated a wave of medium inducing shear stress over the cells. Cells were fixed and stained for the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 32 publications
1
74
0
Order By: Relevance
“…This conclusion regarding the regulation of expression of COX-2 by shear, however, is based upon studies using short periods of shear stress, which may be perceived by cells as an inflammatory insult that resolves with time. Previous work from our group has shown that chronic exposure to shear stress (up to 7 d) is not associated with increases in COX-2 expression in porcine aortic endothelial cells (25). Here we confirm our earlier observations, showing that COX-1, but not COX-2 immunoreactivity was abundant in human aortic endothelial cells cultured under static conditions (Fig.…”
supporting
confidence: 92%
“…This conclusion regarding the regulation of expression of COX-2 by shear, however, is based upon studies using short periods of shear stress, which may be perceived by cells as an inflammatory insult that resolves with time. Previous work from our group has shown that chronic exposure to shear stress (up to 7 d) is not associated with increases in COX-2 expression in porcine aortic endothelial cells (25). Here we confirm our earlier observations, showing that COX-1, but not COX-2 immunoreactivity was abundant in human aortic endothelial cells cultured under static conditions (Fig.…”
supporting
confidence: 92%
“…Moreover, cells in the central region were not aligned, whereas cells in the periphery were elongated and aligned in the direction of the flow ( Figure 3C) as described previously. 40,41 We conclude that the orbital flow system generates spatially distinct flow fields and that cells in the center display morphological and transcriptional features that are characteristic of the response to disturbed flow. We used the orbital shaker platform to determine whether the application of disturbed or undisturbed flow for Figure 3C and Figure IIA in the online-only Data Supplement).…”
Section: Resultsmentioning
confidence: 83%
“…To test this, we used an orbital shaking platform which generates reproducible spatially separated biaxial (disturbed) and uniaxial pulsatile (undisturbed) flow patterns. [39][40][41] CFD (computational fluid dynamics) analysis demonstrated that orbital shaking generated wall shear stress at the center of the well that had a relatively constant low magnitude but varied rapidly in direction ( Figure 3A). Conversely, the periphery was associated with temporal fluctuations in the magnitude of wall shear stress, a relatively high maximum wall shear stress and relatively uniform direction ( Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…This has been seen in areas such as inducing changes in cell shape and orientation, secretion and organization, proliferation and differentiation, intracellular signaling, cytoskeleton protein production and gene expression, vessel maturation and structure, and barrier functions [37][38][39][40][41][42][43][44][45][46][47] . The current in vitro methods for forming endothelial tubes generally rely on endothelial cells' (ECs) self-organization with or without mesenchymal cells in extracellular matrix (ECM) (type I collagen, fibrin, or Matrigel) [48][49][50][51][52][53][54] .…”
Section: Long-term Cell Culturementioning
confidence: 99%